Fine needle aspiration cytology study of HIV lymphadenopathy and its correlation with CD4 count - Khiste, Jayshree; Shete, Smita; Deshpande, Nandkumar; Pandit, Gopal; Matkari, Pushkar (International Journal of Research in Medical Sciences, 2017)
Background: HIV-AIDS is considered as a worldwide pandemic with an epicentre in Asia. Lymphadenopathy is the commonest manifestation observed in HIV-AIDS. Although multiple studies have been conducted in western countries, there is need for further studies to evaluate the causes of lymphadenopathy in Indian setting. So the FNAC study of HIV lymphadenopathy and its correlation with CD4 counts was carried out. Methods: Two yrs. observational study was carried out at the Tertiary care centre from Jan 2013 to Dec 2014. All the patients of HIV lymphadenopathy during this period were included in the study. History and clinical details were obtained from medical records. Thorough clinical examination was done in all cases. Thereafter Fine needle aspiration cytology (FNAC), both guided and unguided was performed, as needed. Smears were fixed and stained with H & E stain & special stains, as required. CD4 counts were carried out at the antiretroviral treatment (ART) centre. Results: Out of 64 cases, Tuberculosis (TB) lymphadenitis was the most common lesion with 47.05% cases & its mean CD4 count was 329/ul. There were 4 cases of malignancy; two were that of primary malignancy - lymphoma and other two were metastasis from epithelial malignancies. Conclusions: FNAC is a simple and rapid investigative technique to differentiate and diagnose various causes of lymphadenopathy. TB lymphadenitis is the most common lesion associated with HIV positive patients. CD4 counts correlate well with underlying lymph node pathology, TB lymphadenitis being common in CD4 range of 200-500/ul and HIV associated malignancies seen in CD4 count less than 100/ul.